2013
DOI: 10.1017/mdh.2012.83
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Injuries: Social Change and Development

Abstract: In the course of the twentieth century road traffic injuries (RTIs) became a major public health burden. RTI deaths first increased in high-income countries and declined after the 1970s, and they soared in low-and middle-income countries from the 1980s onwards. As motorisation took off in North America and then spread to Europe and to the rest of the world discussions on RTIs have reflected and influenced international interpretations of the costs and benefits of 'development', as conventionally understood. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…This figure is in the same league as tuberculosis, which accounted for 1.3 million deaths globally in 2012 as reported by the WHO (Borowy 2013;WHO, 2013). Moreover, in LMICs, deaths from RTIs are actually increasing, especially among pedestrians and motorcyclists.…”
Section: Introductionsupporting
confidence: 54%
“…This figure is in the same league as tuberculosis, which accounted for 1.3 million deaths globally in 2012 as reported by the WHO (Borowy 2013;WHO, 2013). Moreover, in LMICs, deaths from RTIs are actually increasing, especially among pedestrians and motorcyclists.…”
Section: Introductionsupporting
confidence: 54%
“…According to the fact that deaths from accidents occur in the early and middle age of an individual, the impact of such kind of mortality on life expectancy and economic burden caused by it is inevitable (3,4) . Annually, 1.2 million people lose their lives due to traffic accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown a positive association between increased income and the frequency of alcohol consumption, particularly among women (McKee et al, 2000;Michalak, Trocki, & Bond, 2007;WHO, 2014). Further, increased motorisation increases everyone's exposure to road traffic crashes (Borowy, 2013;Sebego et al, 2014;Zhang, Tsimhoni, Sivak, & Flannagan, 2010). Research into alcohol-impaired driving, riding and walking is therefore necessary to provide empirical information to guide in formulating road safety education, policies and interventions to forestall a potential upsurge of alcoholimpaired driving, riding and walking that might arise as Ghana journeys through the trajectory of fast economic development.…”
Section: Extent Of Motorisation In Ghanamentioning
confidence: 99%
“…Ghana has been recently classified as a Lower Middle Income Country (WHO, 2014) and there is an expectation that motorisation will continue to increase, along with lifestyle changes favouring an increase in the use of alcohol (Borowy, 2013).…”
Section: Types Of Alcoholic Drinks Sold In Ghanamentioning
confidence: 99%
See 1 more Smart Citation